Pengaruh Konsentrasi dan Jenis Bahan Pembawa KMnO₄ (Kalium Permanganat) Sebagai Absorben Etilen Terhadap Kualitas Tomat (Lycopersicum esculentum Mill) - Khasbullah, Fizzaria; Yatmin; Sekar Ayu Cahyaningrum; Rakhmiati (Politeknik Negeri Lampung, 2025)
This research aims to determine the effect of providing various concentrations and types of appropriate KMnO₄ carrier material on tomato quality, as well as the interaction between the two. This research used the experimental method Complete Randomized Block Design (RAKL), arranged factorially, namely: (1) KMnO₄ concentration (k) consisting of 3 levels, namely: 0% (Control) (k₀), 5% (25 g/500 ml) (k₁), 10% (50 g/500 ml) (k₂), (2) The type of KMnO₄ carrier material (b) consists of 3 levels, namely: wood shavings (b₁), wood charcoal (b₂), and bricks (b₃ ). Data from observations in the Least Significant Difference (BNT) test at the 5% level. The research results showed that administering various concentrations of KMnO₄ had a real effect on vitamin C levels. The best KMnO₄ concentrations were KMnO₄ 10% and 5%. The use of various types of KMnO₄ carrier materials had no significant effect on all observed variables. The combination of KMnO₄ concentration and different types of carrier material had a real influence on the organoleptic tests observed, namely the color and taste of tomatoes. There is an interaction between various KMnO₄ concentrations and the type of KMnO₄ carrier material on the 8th day hardness level.